Báo cáo trình bày sơ kết 03 năm thực hiện Kế hoạch tài chính quốc gia và vay, trả nợ công 05 năm giai đoạn 2021-2025 - Chính phủ (2023)
Toàn văn Báo cáo trình bày sơ kết 03 năm thực hiện Kế hoạch tài chính quốc gia và vay, trả nợ công 05 năm giai đoạn 2021-2025.